Acute Telogen Effluvium in a Patient After SARS CoV-2 (Covid-19) (Research, Society and Development, 2024)
Objective: This research aims to determine whether there is an association between COVID-19 and acute telogen effluvium, as well as whether the severity of the disease influences the incidence of this phenomenon. Method: Cross-sectional cohort study, quantitative-qualitative, descriptive, focusing on collect and analyze data by applying a questionnaire using the Google Forms® platform. Result: 122 academics participated in the study, of which 84.8% were between 18 - 34 years old, with 69.7% between 18 and 24 years old and 15.2% between 24 and 34 years old. Among them, 68.7% tested positive for COVID-19, with 31.3% testing positive once again. Regarding symptoms, 87.9% had mild symptoms. Regarding the time of infection, more than 80% had an infection time of between 1 and 2 weeks, followed by 14.1% between 2 and 3 weeks. Of the behaviors during the pandemic, 75.8% presented anxiety and 66.7% presented stress. Hair loss was present in more than half of the population after infection (53.5%), with 42.7% experiencing hair loss within one month, and 17.2% within 3 months after infection. The hair loss time was longer than 2 months. Only 23.2% sought help and received treatment.  Only 26.3% had a history of hair loss before the infection. And the form of distribution of the fall was presented by the majority of 53.5% as diffuse. Conclusion: The study reported a high prevalence of post-COVID-19 alopecia, highlighting the need for greater insight into the mechanisms underlying this dermatological phenomenon.